2015
DOI: 10.1021/ef5024753
|View full text |Cite
|
Sign up to set email alerts
|

Waste Gypsum Board and Ash-Related Problems during Combustion of Biomass. 1. Fluidized Bed

Abstract: This paper is the first in a series of two describing the use of waste gypsum boards as an additive during combustion of biomass. This paper focuses on experiments performed in a bench-scale bubbling fluidized-bed reactor (5 kW). Three biomass fuels were used, i.e., wheat straw (WS), reed canary grass (RC), and spruce bark (SB), with and without addition of shredded waste gypsum board (SWGB). The objective of this work was to determine the effect of SWGB addition on biomass ash transformation reactions during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In the previous paper in this series, interactions between SWGB and the formed ash was seen, and it was furthermore concluded that SWGB can be used as an additive against operational problems during combustion of phosphorus-poor biomass in a fluidized bed . The conditions in the fluidized bed used in that study were mainly oxidizing, and the temperature is very stable which may impair the decomposition of SWGB.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…In the previous paper in this series, interactions between SWGB and the formed ash was seen, and it was furthermore concluded that SWGB can be used as an additive against operational problems during combustion of phosphorus-poor biomass in a fluidized bed . The conditions in the fluidized bed used in that study were mainly oxidizing, and the temperature is very stable which may impair the decomposition of SWGB.…”
Section: Introductionmentioning
confidence: 69%
“…The fixed bed combustion experiments in small and large scale both show a statistically significant increase in SO 2 of 100% or more with addition of SWGB. In the previous study using a bubbling fluidized bed (BFB), SWGB addition to RG showed a statistically uncertain increase in SO 2 whereas little or no effect on SO 2 could be observed for WS and SB. The fuel blends used in the BFB experiments contained more SWGB for RG (2 wt %) and WS (2 and 3 wt %); and a similar level for SB (1 wt %) than the fuel blends used in the fixed bed experiments.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Phone: +86-10-68984448; Fax: +86-10-68984448; E-mail: yaoxiaolong@btbu.edu.cn Citric acid residue (CAR) is a typical by-product in the process of citric acid production. Over 2 million tons of CAR are produced in China each year (Ma et al, 2017) and mainly treated through preparation of building materials as the additives or production of feed (Mironiuk et al, 2012;Piotrowska et al, 2015;Juliastuti et al, 2017). Nevertheless, AC has seldom been fabricated based on CAR (CAR-AC).…”
Section: Introductionmentioning
confidence: 99%